Development of Test Instruments to Analyze Higher-Order Thinking Skills Through Science-Based Literacy Learning - Qisthi Fariyani; Hamdan Hadi Kusuma (STKIP Singkawang, 2021)
Higher-order thinking skills are essential skills for a pre-service teacher to have. This study aims to develop the instrument and measure the higher-order thinking skills pre-service physics teacher UIN Walisongo Semarang with science literacy-based learning using the High Order Thinking Skills instrument. The data collection method used was a test, consisting of 20 selected questions with open reasons; structured interviews with lecturers and pre-service physics teachers; and documentation to collect pre-service physics teachers’ data required for research. The test instrument developed by reacherchers and validated by expert in the field of evaluation and physics. The instrument developed was in the form of questions grids, test questions, answer keys, scoring and assessment guidelines, and guidelines for the interpretation of high order thinking skills. The results of product development obtained 14 test items representing four indicators on Simple Harmonic Motion material. The results showed that the higher-order thinking skills of pre-service physics teachers were in the poor category, with an average percentage of 39%. The highest thinking skills are in the indicators determining the period and frequency of vibrations in simple harmonic motion that is in the good category with a percentage of 60.8%. The lowest thinking skills are on the indicator of analyzing energy in simple harmonic moving objects, which are in the inferior category with a percentage of 12.8%. The results of the research show that the higher-order thinking skills of pre-service physics teachers are still low, so that lecturers need to follow up to improve higher-order thinking skills of pre-service physics teachers UIN Walisongo Semarang.